On Survey of the Some Wave Solutions of the Non-Linear Schrodinger Equation (NLSE) in Infinite Water Depth - Yazgan, Tugba; Yel, Gulnur; Celik, Ercan; Bulut, Hasan (Gazi Univ, 2023)
In this work, we use two different analytic schemes which are the Sine-Gordon expansion technique and the modified exp (-O(?))-expansion function technique to construct novel exact solutions of the non-linear Schrodinger equation, describing gravity waves in infinite deep water, in the sense of conformable derivative. After getting various travelling wave solutions, we plot 3D, 2D and contour surfaces to present behaviours obtained exact solutions.
Keywords: The sine-gordon expansion technique; The modified exp (-O(?))-expansion function technique; Conformable derivative; Non-linear schrodinger equation (NLSE)